Bryophytes hold a larger gene family space than vascular plants - Dong, Shanshan; Wang, Sibo; Li, Linzhou; Yu, Jin; Zhang, Yongxia; Xue, Jia-Yu; Chen, Hengchi; Ma, Jianchao; Zeng, Yuying; Cai, Yuqing; Huang, Wei; Zhou, Xuping; et al. (My University, 2025)
After 500 million years of evolution, extant land plants compose the following two sister groups: the bryophytes and the vascular plants. Despite their small size and simple structure, bryophytes thrive in a wide variety of habitats, including extreme conditions. However, the genetic basis for their ecological adaptability and long-term survival is not well understood. A comprehensive super-pangenome analysis, incorporating 123 newly sequenced bryophyte genomes, reveals that bryophytes possess a substantially greater diversity of gene families than vascular plants. This includes a higher number of unique and lineage-specific gene families, originating from extensive new gene formation and continuous horizontal transfer of microbial genes over their long evolutionary history. The evolution of bryophytes' rich and diverse genetic toolkit, which includes new physiological innovations like unique immune receptors, likely facilitated their spread across different biomes. These newly sequenced bryophyte genomes offer a valuable resource for exploring alternative evolutionary strategies for terrestrial success.